The Influence of Current Ratio and Return on Equity on Stock Prices in the Company Pt Adaro Energy Indonesia Tbk Period (2013-2022) - Helda Fajriani; Jeni Irnawati (International Journal of Educational and Life Sciences, 2024)
Finding out how return on equity and the current ratio impact stock prices is the aim of this research. The profitability and liquidity ratios, as determined by the current ratio and return on equity, respectively, are the study's independent variables, while the stock price is its dependent variable. A quantitative research approach is used in this investigation. The population and sample for the research were drawn from the 2013–2022 annual financial analysis report of PT Adaro Energy Indonesia Tbk. Descriptive statistical tests, multiple linear regression analysis, coefficient of determination tests, conventional assumption tests (autocorrelation, heteroscedasticity, multicollinearity, and normality tests), and hypothesis tests (T-tests and F-tests) are among the data analysis methods that are performed using the IBM SPSS Statistic Version 26 software. The study's findings indicate that although return on equity has a significant influence on stock price, the current ratio has no effect at all. At the same time, stock price are significantly impacted by the current ratio and return on equity. According to the results of the coefficient of determination test, the dependent variable stock price is explained by the current ratio and return on equity in 89.1% of cases, with the remaining 10.9% resulting from variables not included in this study. The R square value is 0.891.